OX40 agonist stimulation increases and sustains humoral and cell-mediated responses to SARS-CoV-2 protein and saRNA vaccines - Duhen, Rebekka; Beymer, Michael; Jensen, Shawn M.; Abbina, Srinivas; Abraham, Suraj; Jain, Nikita; Thomas, Anitha; Geall, Andrew J.; Hu, Hong-Ming; Fox, Bernard A.; Weinberg, Andrew D. (Frontiers in Immunology, 2022)
To prevent SARS-CoV-2 infections and generate long-lasting immunity, vaccines need to generate strong viral-specific B and T cell responses. Previous results from our lab and others have shown that immunizations in the presence of an OX40 agonist antibody lead to higher antibody titers and increased numbers of long-lived antigen-specific CD4 and CD8 T cells. Using a similar strategy, we explored the effect of OX40 co-stimulation in a prime and boost vaccination scheme using an adjuvanted SARS-CoV-2 spike protein vaccine in C57BL/6 mice. Our results show that OX40 engagement during vaccination significantly increases long-lived antibody responses to the spike protein. In addition, after immunization spike protein-specific proliferation was greatly increased for both CD4 and CD8 T cells, with enhanced, spike-specific secretion of IFN-gamma and IL-2. Booster (3rd injection) immunizations combined with an OX40 agonist (7 months post-prime) further increased vaccine-specific antibody and T cell responses. Initial experiments assessing a self-amplifying mRNA (saRNA) vaccine encoding the spike protein antigen show a robust antigen-specific CD8 T cell response. The saRNA spike-specific CD8 T cells express high levels of GrzmB, IFN-gamma and TNF-alpha which was not observed with protein immunization and this response was further increased by the OX40 agonist. Similar to protein immunizations the OX40 agonist also increased vaccine-specific CD4 T cell responses. In summary, this study compares and contrasts the effects and benefits of both protein and saRNA vaccination and the extent to which an OX40 agonist enhances and sustains the immune response against the SARS-CoV-2 spike protein.